DETERMINANTS OF ENTREPRENEURIAL INTENTIONS AND THE INFLUENCE ON ENTREPRENEURIAL BEHAVIOR OF STUDENTS AND GRADUATES OF THE ENTREPRENEURSHIP PROGRAMS IN THAILAND - Charuwannadetch, Natha; Pinvanichkul, Tippawan (RMUTT Global Business and Economics Review, 2022)
It is assumed that behavioral intention predicts the entrepreneurial behavior of a person while the intention is influenced by the personal Attitude Toward Behavior (ATT), Subjective Norms (SN), and Perceived Behavioral Control (PBC) which follows the Theory of Planned Behavior (TPB). This study aims to explain entrepreneurial intentions and the entrepreneurial behavior of students and graduates of the Entrepreneurship Programs in Thailand with the influence of ATT SN and PBC. Four hundred samples of questionnaire results were collected from students and graduates of the entrepreneurship program of the universities in Thailand. Structural Equation Model (SEM) is applied. Result of the confirmatory factor analysis (CFA) and the correlation between variables within the SEM hypothesis support the hypothesis of measurement model and the structural model. The results of this study indicate a direct effect of the personal ATT, SN, and PBC as the antecedents of entrepreneurial intention and indirect effect on entrepreneurial behavior through entrepreneurial intention. The hypothesis of the direct effect of PBC on entrepreneurial behavior was rejected. The results reflecting that entrepreneurship program could play an important role in the development of entrepreneurship intention by providing students the competency and skills necessary to be an entrepreneur whether by creating a learning atmosphere to help promoting positive attitude towards entrepreneurship behavior. Business practicing or entrepreneurial workshop or laboratory for improvement of individual perception of entrepreneurial behavioral control should be encourage.